Revolutionizing Workflows: The Role of Efficiency in Organizational Success - Sundari, Pipit; Felas Silitonga, Grace; Setiyarti, Tettie (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2024)
This research investigates the impact of workflow optimization and resource management on organizational success at PT. Citra Shipyard, with a particular focus on the mediating role of operational efficiency. Using a quantitative research design and random sampling of 80 employees, data were collected through structured questionnaires and analyzed with Smart PLS (Partial Least Squares Structural Equation Modeling). The study found that both workflow optimization and resource management significantly influence operational efficiency, which, in turn, has a strong effect on organizational success. Specifically, workflow optimization and resource management were shown to enhance operational efficiency, thereby driving greater organizational success. These results emphasize the importance of integrating effective workflow and resource management strategies to improve operational outcomes and achieve sustained competitive advantage in the shipbuilding industry. This research provides valuable insights for PT. Citra Shipyard to refine its operational practices and enhance overall performance.